Analisis Gangguan Makan dan Status Gizi Pada Orang Dewasa Selama Pandemi Covid-19 di Indonesia: Analysis of Eating Disorders and Nutritional Status among Adults During the Covid-19 Pandemic in Indonesia - Wiji indah Lestari; Arif Sabta Aji; Yhona Paratmanitya (Universitas Airlangga, 2025)
Background: The COVID-19 pandemic and the implementation of Large-Scale Social Restrictions (LSSR) in Indonesia have raised concerns regarding mental health and behavioral changes, including eating patterns. Psychological stress and uncertainty related to social and economic limitations may increase the risk of eating disorders and ultimately affect nutritional status. Objectives: This study aims to investigate the relationship between eating disorders and nutritional status among adults during the COVID-19 pandemic in Indonesia. It also tries to identify factors influencing both conditions. Methods: This study used a cross-sectional research design. Secondary data were obtained from the IndoNutriLife-COVID-19 online survey, involving 287 adults. Collected variables included sociodemographic characteristics, eating disorders, nutritional status, and LSSR status. Data were analyzed using THE Chi-square test and logistic regression analysis. Results: Nearly half of the participants (49.8%) lived in LSSR areas. A total of 16% of participants experienced eating disorders, while the others were underweight (8.4%), overweight (25.4%), and obese (9.1%). LSSR status was not significantly associated with eating disorders or nutritional status. Eating disorders and nutritional status did not show a significant relationship. Age and sex were significantly associated with nutritional status (p-value = 0.02; p-value < 0.001). Conclusions: LSSR status is not associated with eating disorders or nutritional status during the COVID-19 pandemic. Maintaining balanced dietary intake and overall well-being remains essential during periods of activity restriction.